Negotiation and agreement between the Umayyad state and the Ahlul Bayt( Alawites) and their supporters (Raparin Journal of Humanities (RJH), 2024)
The name of(Umayyad)comes after the name of their father whose name was"Uayya bin Add shams bin Adbukmanaf.Ma'away bin Abi Sufyan bin Harb this known as the first calipher of Umayyad. According to most of the sources، after Hassan bin Ali's resigned from caliphate،and they made an agreement in 661 Ac/41 H which is known as "A'am Al-jama'a"، Ma'away became the first caliph of Umayyad. Nearly most of the domestic issues had been finished. this kind of agreement had become a tradition among all other Umayyad caliphs that they tried to make such agreement with the family of( A'alawyyah) in order to confirm their rule beside coming to power inherently instead of through consulting system. Therefore Yzid bin Ma'away tried hard to deal with Hussein bin Ali because he thought that his rule will not be more stable and legal until getting Hussein's support.When Abdulmalik bin Marwan became a caliph in Sham inherently while he had a serious struggle with Abdulla bin Zuber، caliph of Hijaz. For the sake of the confirmation and trust of his rule، he tried to make a deal with Muhammed Hanifa bin Ali، and they confirm his rule after the murder of Bin Zuber.